Fourth World: Marxian, Gandhian, Environmental... - RAJINDER CHAUDHARY (Economic and Political Weekly October 15, 2005, 2005)
The idea of the `Fourth World' as enunciated by M P Parameswaran, a leading thinker from Kerala, is a new concept of a post-capitalist society. It can form the basis for Marxists, Gandhians, environmentalists, feminists, socialists, dalits and peace activists to work together. It offers a theoretical space for all these movements.